Milled Rice Quality Evaluation of Some Hope Strain Rice Field Rice (Oryza sativa L.) - Yuriansyah Yuriansyah (Jurnal Penelitian Pertanian Terapan, 2017)
The purpose of this study was to determine the quality of milled rice paddy rice several promising lines. The study was conducted in the village of Banjarrejo District of Batang, East Lampung Regency and Lampung State Polytechnic in November 2012 using a completely randomized design with 10 treatments and three replications. The treatment consisted of 10 new rice paddy promising lines 1. IPB 3S, 2. IPB 4S, 5R IPB 3., 4. IPB6R, 5. IPB117-F-7-2-1, 6. IPB 117-F-7-7 -1, 7. IPB 117-F-14-4-1, 8 IPB 117-F-15-4-1, 9. IPB 117-F-20-1-1, and 10. The IPB 117-F- 80-2-1. The results showed that the quality of milled rice paddy rice several promising lines tested have diversity in terms of: rendemen , milling degree, water content, grain heads, broken grains, brewers grains, grains of red, yellow grain, grain whitewash, and grains. Eight promising lines meet minimum standards milling degree, 10 strains meet the standard of a maximum water content, 2 lines meet minimum standards of grain heads, two lines meet minimum standards of broken grains, 9 strains meet the minimum standards of red grains, 7 strains meet minimum standards yolks, 1 strains meet minimum standards grains whitewash, 10 strains meet the minimum standards of foreign objects, and 6 lines meet minimum standards grains of milled rice quality requirements of quality I ISO 6128: 2008.Keywords: quality of milled rice, promising lines, paddy rice